Il dattiloscritto ritrovato - Armando, David (Il sogno della farfalla, 2024)
The aim of this article is to introduce the edition of the “sixth chapter” of Massimo Fagioli’s Death instinct and knowledge (1972). This final section of the book, hitherto largely unpublished, was initially present in the original typescript, drafted in early 1971 and recently found in Fagioli’s private archive. In order to facilitate the approach to the rediscovered text, this article provides to the reader some essential information about the typescript, its drafting and circulation, and the changes that occurred in the transition to the printed version.